94.0k views
0 votes
PLSSSSSSSSSSS HELPPPP>>> Show work Solve the system y= -x+3 y=3/2x-2

User Dma
by
5.2k points

2 Answers

4 votes

Answer:

x = 2

y = 1

Explanation:

y = -x + 3

y = 3/2x - 2

Put y as -x+3 in the second equation and solve.

-x + 3 = 3/2x - 2

-x - 3/2x = -2 - 3

-5/2x = -5

x = -5 × -2/5

x = 10/5

x = 2

Put x as 2 in the first equation and solve.

y = -(2) + 3

y = 3 - 2

y = 1

User Valexa
by
5.7k points
5 votes

Answer:

x=2, y=1

Explanation:

y= -x+3

y=3/2x-2

Since the two equations are both equal to y, we can set them equal

-x+3=3/2x-2

Add x to each side

-x+x+3=3/2x+x-2

3 = 3/2x+2/2x-2

3 = 5/2x -2

Add 2 to each side

3+2 = 5/2x -2+2

5 = 5/2x

Multiply each side by 2/5

5 *2/5 = 5/2x*2/5

2 =x

Now find y

y =-x+3

y = -2 +3

y =1

User Kiran Shakya
by
5.6k points